Transition countries' and the knowledge-based economy - Švarc, Jadranka (Array, 2004)
The paper is introduction into the Conference Proceeding that elaborates transition countries' moving towards knowledge based economy/society. The need for a new policy paradigm and social change is stressed. The review of conference papers are presented with some policy implications for CEEC.